PAFE: projeto de assistência farmacêutica estudantil - Diniz, Any Carolina Ióca [UNESP]; Alves, Gabrielle Cunha [UNESP]; Furlan, Letícia Cristina [UNESP]; Marin, Marcelo Tadeu [UNESP]; Almeida, Adelia Emilia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Projeto de Assistência Farmacêutica Estudantil (PAFE) is a work developed by students and professors of School of Pharmaceutical Sciences at UNESP-Araraquara that aims to instruct and provide pharmaceutical care to the population. The project develops free activities with schools, companies and also in university campus. Undergraduate pharmacy students participate in the planning and organization of all activities with the help of professors. They are allocated into thematic groups on annual administrations. Some of the themes that comprise the activities are: Anemia, Diabetes, Hypertension, Correct Use of Medicines, Cancer Prevention, First Aid, Food and Health, Parasitic Diseases, Sexual Orientation, Herbal Medicine and Medicinal Plants. PAFE organizes own events or member students participate in orientation activities and carrying out rapid tests in events of other organizations. In the biggest event that PAFE organizes (Semana de Assistência Farmacêutica Estudantil-SAFE) around 250 undergraduate students work as volunteers and perform about 5,000 health care services on each annual event.

O Projeto de Assistência Farmacêutica Estudantil (PAFE) é um trabalho desenvolvido pelos alunos e docentes do curso de Farmácia-Bioquímica da UNESP-Araraquara que tem como objetivo transmitir conhecimento e prestar assistência farmacêutica à população. O projeto desenvolve atividades gratuitas junto a escolas, empresas e também nas unidades do campus. Graduandos do curso de Farmácia-Bioquímica participam do planejamento e organização de todas as atividades, com o auxílio de docentes, sendo divididos em grupos temáticos em gestões anuais. Alguns dos temas que compões as atividades são: Anemia, Diabetes, Hipertensão Arterial, Uso Correto de Medicamentos, Prevenção do Câncer, Primeiros Socorros, Alimentação e Saúde, Doenças Parasitárias, Orientação Sexual, Fitoterapia e Plantas Medicinais. São realizados eventos próprios do projeto ou os alunos integrantes participam de atividades de orientação e realização de exames rápidos em eventos de outras organizações. O maior evento que o PAFE organiza (Semana de Assistência Farmacêutica Estudantil-SAFE) conta com a participação de mais de 250 graduandos como voluntários e realiza cerca de 5 mil atendimentos em cada evento anual.
Keywords: Pharmaceutical care; Attendace; Volunteer; Assistência farmacêutica; Atenção farmacêutica; Trabalho voluntário